Teaching Resilience to Aspiring Educational Leaders - Lamb, Jodi A.; Carver, Lin (Advances in Social Sciences Research Journal, 2020)
Resiliency in practicing and aspiring educational leaders is an attribute that contributes to extended effectiveness and longevity. This pilot study examines research about resiliency and compares the identified methods to those methods employed by university educational leadership programs to support and enhance resiliency development in their candidates. This pilot study examines survey Likert and open-ended responses from thirteen educational leadership programs throughout the United States with a combined total enrollment of over a thousand students. The strategies are divided into four categories based upon the ways that students interact with the resiliency content: concept building, vicarious, problem solving, or relationships. The literature indicated interpersonal and problem solving were the most influential activities recommended for teaching resilience; however, the most frequent types of activities identified by educational leadership programs were vicarious experiences and relationships. The preliminary findings indicate the importance of expanding problem solving experiences. In addition, a more thorough investigation of the role that interpersonal relationships play in developing resilience would be an important area for future study.